Time is money: Life cycle rational inertia and delegation of investment management - Hugh H. Kim; Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
We investigate the theoretical impact of including two empirically-grounded insights in a dynamic life cycle portfolio choice model. The first is to recognize that, when managing their own financial wealth, investors incur opportunity costs in terms of current and future human capital accumulation, particularly if human capital is acquired via learning by doing. The second is that we incorporate age-varying efficiency patterns in financial decisionmaking. Both enhancements produce inactivity in portfolio adjustment patterns consistent with empirical evidence. We also analyze individuals' optimal choice between self-managing their wealth versus delegating the task to a financial advisor. Delegation proves most valuable to the young and the old. Our calibrated model quantifies welfare gains from including investment time and money costs, as well as delegation, in a life cycle setting.
urn:nbn:de:hebis:30:3-324854
Keywords: 330